Growth and Yield of Microgreens in Two Varieties of Curly Lettuce (Lactuca sativa L.) under Different Concentrations of Liquid Organic Fertilizer - Saepurohman, Indra Lesmana (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2025)
INDRA LESMANA SAEPUROHMAN, 2024. Growth and Yield of Microgreens in Two Varieties of Curly Lettuce (Lactuca sativa L.) under Different Concentrations of Liquid Organic Fertilizer. Under the guidance of YAYU SRI RAHAYU, WINDA RIANTI, dan ZAHARA MAHARDIAH. Microgreens are plants that can be cultivated in a short period, having a lifespan longer than sprouts but younger than baby greens, yet possessing higher nutritional content than mature plants. Despite their short lifespan, the provision of additional nutrients during cultivation can enhance the growth and yield of microgreens. This study aims to investigate the growth and yield of microgreens from two lettuce varieties under various concentrations of liquid organic fertilizer (LOF). The method used in this research is an experimental method with a factorial randomized block design (RBD) consisting of two factors. The first factor is the lettuce variety, comprising 2 levels, and the second factor is the concentration of LOF, comprising 4 levels, with 3 repetitions, resulting in 24 experimental units. The treatment effects were analyzed using variance analysis, and if the F-test at the 5% level was significant, further analysis was conducted using Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed interactions between the two lettuce varieties of microgreens and various LOF concentrations on parameters such as germination uniformity, plant height growth rate, fresh weight, chlorophyll content, and phenolic content. Microgreens of the Olga Red lettuce variety with an LOF concentration of 2 ml/l provided the best growth and yield in terms of germination uniformity, plant height growth rate, fresh weight and chlorophyll content. In contrast, microgreens of the New Grand Rapid lettuce variety with an LOF concentration of 6 ml/l showed the best growth in terms of root length, plant height growth rate, and chlorophyll content. Keywords: Microgreens, Curly Lettuce, Liquid Organic Fertilizer, Plant Growth, Antioxidants.